Perancangan Rumah Sakit Khusus Paru-Paru - Trisna, Denny Pandji; Kamil, Erfan M (Universitas Muhammadiyah Palembang, 2023)
Treatment and healing facilities for special lung diseases at the Palembang City Pulmonary Hospital currently in need of increased facilities and total rehabilitation, the current facilities can be said to be relatively minimal. It can be said that it is inadequate when viewed from the facilities and infrastructure available now, for inpatient facilities which are still simple, for ventilation systems only limited by using makeshift media and air ventilation, the physical building and the environment are not well maintained and the circulation of the building is still relatively narrow. Therefore, a Special Lung Hospital is needed which accommodates patients with special lung diseases in South Sumatra, with an emphasis on the physical environment and facilities that can support care in the patient’s health recovery process and create a special scale lung hospital environment. Cities with facilities that support the patient’s adaptation process by involving the effects of environmental management through an emphasis on the concept of Healing Environment.